Transformation And Representation of Dolalak Dance in Purworejo District - Nimas Agustin Purwaningtyas, Nimas Agustin Purwaningtyas; Agus Cahyono; Hartono Hartono (Catharsis, 2024)
Dolalak Dance is a traditional dance originating from Purworejo Regency which was born in 1915 with male dancers. Over time, the Dolalak Dance has transformed in the form of performance and function of the Dolalak Dance performance. This is due to acculturation and cultural assimilation. Researchers are interested in the transformation and representation of Dolalak Dance in Purworejo Regency because it provides benefits including transformation as the identity of the Dolalak Dance group, transformation can increase interest in Dolalak Dance cultural art appreciators. Dolalak dance transformation can meet market demand, Dolalak Dance transformation can maintain the existence of the Dolalak dance itself, Dolalak dance transformation is expected to be able to attract the interest of new dance art appreciators. The formulation of the research problem is: 1. How is the transformation process that occurs in Dolalak Dance in Purworejo Regency 2. How is the representation in the Dolalak Dance performance in Purworejo Regency? The study aims to analyze the transformation of the form of the Dolalak Dance Performance and representation in the Dolalak Dance performance in Purworejo Regency. This study uses a qualitative research method with an interdisciplinary approach, namely sociology of art, ethnochoreology, and art education. Data collection techniques are carried out using observation, interview, and documentation techniques. Data validity techniques use data triangulation.The results of the study revealed that the form of Dolalak Dance in Purworejo Regency experienced 4 stages of transformation. (1) The first stage in 2003 Bedhol Dance (2) The second stage in 2012, Dolalak Lentera Jawa I Dance (3) The third stage in 2014 Dolalak Lentera Jawa II Dance, Dolalak Sri Lestari Dance. Representation in the Dolalak Dance is reflected in the transformation of the Dolalak Dance form, and the meaning contained in the Dolalak Dance. The suggestion in this study is that the Dolalak Sri Lestari Dance Group and the community are expected to continue to preserve the Dolalak Dance with innovations that are still by Javanese cultural traditions without eliminating the essence of the Dolalak Dance.